Secret valentine - Stock, Catherine (New York : Bradbury Press ; Toronto : Collier Macmillan Canada, 1991)
A child makes valentines for her family and then adds a special name to her list. On Valentine's Day she receives a secret valentine in return.
Elementary School Library Collection (Bro-Dart)
School Library Journal
1.5
K-3
Keywords: Valentine's Day -- Fiction; Afro-Americans -- Fiction; Valentine's Day -- Fiction